Comparative Evaluation of Reducing Potential of Flowers from Two Catharanthus roseus Subspecies - Shahwar, Durre; Mansha Chohan, Muhammad; Yasmeen, Asma; Saeed, Afifa; Sana, Uzma; Bukhari, Sana; Ara, Gulshan; Akmal Khan, Muhammad (Asian Journal of Chemistry, 2012)
Catharanthus roseus L. (Vinca rosea) flowers have wound healing, antiasthmatic properties and flower extract had also been used for eyewash in infants. The aim of the present study is to demonstrate antioxidant potential of the flower extracts of Catharanthus roseus subspecies. The flowers of two Catharanthus roseus subspecies (pink and white) were extracted, by soaking the fresh chopped material in n-hexane, chloroform, methanol and ethanol. All the extracts were evaluated for 1,1-diphenyl-2-picrylhydrazyl (DPPH) free radical, ferric reducing ability of plasma assays. Total phenolics and flavonoids were also estimated for all the extracts. The reducing potential of the extracts ranged from 91.96 ± 1.26 to 20.53 ± 1.04 % in DPPH assay while 0.307 ± 0.05 to 0.572 ± 0.01 mmoles in ferric reducing ability of plasma assay phenolics and flavonoids estimation show that methanol and ethanol extracts contain large amount of phenolics and flavonoids. A linear relationship was found in between antioxidant potential and phenolic content of the extracts of white and pink flowers (R2 = 0.902) and (R2 = 0.819) respectively.